Low-cost composite film triboelectric nanogenerators for a self-powered touch sensor. Issue 13 (13th March 2023) - Fan, Jie-Cheng; Tang, Xin-Gui; Sun, Qi-Jun; Jiang, Yan-Ping; Li, Wen-Hua; Liu, Qiu-Xiang
Abstract : The signal of a self-powered touch sensor based on a TENG is processed to control LEDs. Abstract : In the last two decades, nanogenerators have been studied inorder to solve the power supply problems of electronic devices. Triboelectric nanogenerators (TENGs) have gained widespread attention due to their excellent properties and wide range of applications. However, previous studies frequently ignored numerous application-related issues and even wasted some of the benefits of the TENG itself in favor of enhanced performance. Here, we propose a TENG based on BaTiO3 (BTO)–polydimethylsiloxane (PDMS) composite films with low cost and simple preparation, where its maximum output performance is obtained when the mass proportion of BTO to PDMS is 40%. In addition, we demonstrate how the single-electrode TENG may be used as a self-powered touch sensor that can communicate with a microcontroller unit (MCU) to turn LED lights on and off. This practical example will provide a valuable reference for the application of low-cost self-powered sensors in wearable devices, Internet of Things, human–machine interactions and other fields. Furthermore, we discovered a number of issues that were rarely or never addressed in previous studies and provide some solutions, such as a signal processing method for a TENG-based self-powered sensor. It serves as a foundation for future investigations on the performance assessment and application of TENGs.